META-ANALISIS PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA - Novi Indah Lestari; Abdul Razak; Lufri Lufri; Zulyusri Zulyusri; Fitri Arsih (Bioilmi: Jurnal Pendidikan, 2022)
The purpose of this study was to analyze the effect of using the Teams Games Tournament (TGT) learning model on student learning outcomes. This research method is a meta-analysis by examining data sources originating from national or international journals published in the last seven years (2014-2021). This research begins with formulating the topic to be studied, then formulating the problem and research objectives, at the next stage collecting relevant articles to collect data. The data was obtained from online journal searches through Google Scholar. The keywords used are "Teams Games Tournament learning model" and "learning outcomes". From the search results there are 20 articles. Data were obtained and reanalyzed using quantitative methods. Based on the results of the analysis of the Teams Games Tournament learning model, it is proven to be able to improve student learning outcomes with significant results after being given treatment, which is 69.93% compared to the results before being given treatment, which is 55.75% so that it increases by 14.18%.